2021
DOI: 10.3389/fmed.2020.615015
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Findings After Intravitreal Ranibizumab in Patients With Coats Disease

Abstract: The aim of this retrospective study was to describe the vascular features in eyes with Coats disease, using optical coherence tomography angiography (OCTA), at baseline and after 3 monthly intravitreal injections of ranibizumab. Fifteen eyes of 15 consecutive patients affected by Coats' disease were recruited in this study. All patients underwent the best-corrected visual acuity (BCVA) evaluation, fundus examination, fluorescein angiography (FA), indocyanine green angiography (ICGA), multicolor imaging, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In agreement with the findings of Cennamo et al and Hautz et al, the retinal vascular flow patterns were not convincingly different following anti-VEGF treatment. 6 , 9 However, the choroidal vascular density appeared increased following anti-VEGF therapy, according to the selected slabs. As OCTA studies have shown that anti-VEGF agents result in decreased choroidal density, presumably due to pharmacological vasoconstriction, 10 the relative improvement in choroidal slabs on our OCTA figures may be the results of artifact or may imply a possible role of choroidal vasculature in pathology of Coats' disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings of Cennamo et al and Hautz et al, the retinal vascular flow patterns were not convincingly different following anti-VEGF treatment. 6 , 9 However, the choroidal vascular density appeared increased following anti-VEGF therapy, according to the selected slabs. As OCTA studies have shown that anti-VEGF agents result in decreased choroidal density, presumably due to pharmacological vasoconstriction, 10 the relative improvement in choroidal slabs on our OCTA figures may be the results of artifact or may imply a possible role of choroidal vasculature in pathology of Coats' disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard test for diagnosis is FA. Besides, OCT can identify macular edema and exudates 19 . This patient was consistent with stage 2B Coats disease according to Shields' Classi cation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the vascular supply of the SCP and DCP, with the DCP being distal vessels with weaker walls and more likely to be disrupted in Coats disease [ 84 ]. In another series by Cennamo et al, the authors noted capillary hypoperfusion with an increased FAZ area in the SCP, along with irregularly dilated small perifoveal vessels and a loss of collateral branches and increased vascular rarefaction, were noted in the DCP [ 85 ]. In eyes with macular fibrosis, a disrupted vascular network and coarse macula vessels may be observed using OCTA [ 82 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
“…In eyes with macular fibrosis, a disrupted vascular network and coarse macula vessels may be observed using OCTA [ 82 ]. However, it is important to note that subretinal exudate may lead to obscuration of choriocapillaris (CC), and manual segmentation of OCTA images in a patient with macula exudates may be required to accurately visualize blood vessels [ 84 , 85 ]. In addition, OCTA of Coats disease may also reveal an irregular FAZ with crossing vessels on both the SCP and DCP [ 10 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation